Association between Sclerosing Cholangitis and Paget Disease: Diagnostic Difficulties - Sabbah, Meriam; Bibani, Norsaf; Trad, Dorra; Ouakaa, Asma; Elloumi, Héla; Gargouri, Dalila (Journal of Spleen And Liver Research, 2018)
A rare case of association between primary sclerosing cholangitis and Paget's disease emphasizing the diagnostic difficulties in front of increased alkaline phosphatase is reported. The association between sclerosing cholangitis and Paget's disease wasn’t yet described and could thus be coincidental. However, our observation underlines the benefit of dosing ALP isoenzyme to characterize the bone or hepatic origin of ALP and therefore, help to guide the diagnosis.
Keywords: Cholangitis; Paget disease; alkaline phosphatase